ANALYSIS OF THE EFFECT OF GOVERNMENT EXPENDITURE IN THE AGRICULTURAL SECTOR, AGRICULTURAL SECTOR INVESTMENT AND AGRICULTURAL SECTOR LABOR ON GROSS REGIONAL DOMESTIC PRODUCT (GRDP) IN THE AGRICULTURAL SECTOR IN NAGEKEO REGENCY - Katarina Wea Logho; Cicilia Apriliana Tungga; Muhammad Alwan Habibi Mushlih (Universitas Dharmawangsa Medan, 2026)
This study aims to determine the extent of influence of government expenditure in the agricultural sector, agricultural investment, and agricultural labor on the gross regional domestic product (GRDP) in the agricultural sector in Nagekeo Regency. This study uses quantitative descriptive research, with the analysis method used being multiple linear regression with secondary time series data. The results of this study indicate that, partially, the variables of government expenditure in the agricultural sector and investment in the agricultural sector have a positive and significant effect on the gross regional domestic product (GRDP) of the agricultural sector in Nagekeo Regency. The variable of agricultural labor in the agricultural sector does not have a positive and significant effect on the gross regional domestic product (GRDP) of the agricultural sector in Nagekeo Regency. Simultaneously, or collectively, the variables of government expenditure in the agricultural sector, investment in the agricultural sector, and labor in the agricultural sector have a positive and significant effect on the gross regional domestic product (GRDP) of the agricultural sector in Nagekeo Regency. Keywords: Government Expenditure in the Agricultural Sector, Investment in the Agricultural Sector, Labor in the Agricultural Sector, Gross Regional Domestic Product (GRDP) of the Agricultural Sector